Effectiveness of School-Based Interventions in Europe for Promoting Healthy Lifestyle Behaviors in Children - Archontoula Drouka; Dora Brikou; Céline Causeret; Nur Al Ali Al Malla; Stéphane Sibalo; Concha Ávila; Gabriela Alcat; Anastasia E. Kapetanakou; Patricia Gurviez; Nawel Fellah-Dehiri; Marine Masson; Meropi D. Kontogianni; et al. (MDPI AG, 2023)
The objective of this narrative review was to summarize existing literature on the effectiveness of school-based interventions, implemented in Europe, under the aim of promoting healthy lifestyle behaviors in children (6-10 years old). A search of PubMed, Scopus, EFSA and Google Scholar databases was performed for studies published from January 2016 to June 2022. Specific search terms and exclusion criteria were used. Based on the results, diet and physical activity interventions had favorable effects on a series of health outcomes, including anthropometric parameters, biomarkers, eating behavior and self-efficacy. Diet-only interventions had a positive impact specifically on eating habits, mostly on water consumption. Most successful interventions lasted for 1 school year, and they were characterized by parental involvement and teachers' training.